Revisiting endogeneity among foreign direct investment, economic growth and stock market development: Moderating role of political instability - Mohammad Enamul Hoque; Tahmina Akhter; Noor Azuddin Jakob (Cogent Economics & Finance, 2018)
This study investigates the endogeneity among foreign direct investment, economic growth, and stock market development, along with the moderating role of political instability on the relationship among foreign direct investment, economic growth, and stock market development. The study employs selected macroeconomic variables data for the period of 1993-2016 with Auto Regressive Distributed Lag (ARDL) system and hierarchical regression approach for hypothesis testing. This study discovers that there are short-run and long-run association among economic growth, foreign direct investment, and stock market development. In the long run, only unidirectional relationship exists among economic growth, foreign direct investment, and stock market development. However, in the short-run, bidirectional relationship is evident between economic growth and stock market development. This study reveals that foreign direct investment partially mediates the relationship between economic growth and stock market development; and political instability negatively moderates the economic growth and stock market development nexus, the foreign direct investment and stock market development nexus, and the economic growth and foreign direct investment nexus. Therefore, this study suggests that political stability is a must for Bangladesh to achieve stock market development, to increase the foreign direct investment inflows, and to achieve long term sustainable growth.
Keywords: 330; stock market; economic growth; FDI; political instability; Bangladesh